An Eutectic Gel Based on Polymerizable Deep Eutectic Solvent with Self‐Adhesive, Self‐adaptive Cold and High Temperature Environments. Issue 7 (25th January 2023) - Wang, Rixuan; Chen, Picheng; Zhou, Xinjie; Sun, Luyang; Wang, Guoqing; Liu, Yuetao; Gao, Chuanhui
Abstract: Ionic conductors have a wide range of development prospects in the field of flexible wearable electronics. The polymerizable deep eutectic solvent is more economical, resistant to extreme temperature, and less toxic than the traditional hydrogels and ionic liquids. In this paper, the supramolecular eutectic gel is prepared by introducing glycol/choline chloride deep eutectic solvent into acrylamide/choline chloride deep eutectic solvent as "hydrogen bond cross‐linking density regulator". Deep eutectic solvents give eutectic gels the ability to resist the low (‐25 °C) and high (60 °C) temperatures. By introducing 2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid into the gel, the adhesion ability of gel on copper sheet can reach 90 kPa and shows good reusability. Due to the complex hydrogen bond interaction in the gel, it has good mechanical properties (strain up to 2300%, stress up to 0.21 MPa). In addition, the ionic conductivity of the gel can reach 0.22 ms cm −1 due to the presence of choline chloride. In addition, since the polymerization is triggered quickly under UV light, this allowed us to print gels of any shape on any surface. Such deep eutectic gels with self‐adhesion, intrinsic conductivity, excellent mechanical properties and extreme temperature resistance may have a wide range of applications in the field of motion sensors. Abstract : A eutectic gel is prepared by using two kinds of deep eutectic solvents, which can withstand low temperature and high temperature. The adhesion ability is introduced into the eutectic gel by introducing 2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid. The eutectic gel will shine in the field of human motion monitoring.